Epitranscriptomic m6A regulation following spinal cord injury. Issue 3 (3rd December 2020) - Xing, Lingyan; Cai, Yunyun; Yang, Tuo; Yu, Weiwei; Gao, Mengdie; Chai, Rui; Ding, Sujun; Wei, Jinhuan; Pan, Jingying; Chen, Gang
Abstract: RNA methylation is involved in multiple physiological and pathological processes. However, the role of RNA methylation in spinal cord regeneration has not been reported. In this study, we find an altered m6A (N6‐methyladenosine) RNA methylation profiling following zebrafish spinal cord injury (SCI), in line with an altered transcription level of the m6A methylase Mettl3. Interestingly, many of the differential m6A‐tagged genes associated with neural regeneration are hypomethylated, but their transcription levels are upregulated in SCI. Moreover, we find that METTL3 may be important for spinal cord regeneration. We also show a conserved feature of METTL3 changes in mouse SCI model, in which the expression of METTL3 is increased in both astrocytes and neural stem cells. Together, our results indicate that m6A RNA methylation is dynamic and conserved following SCI and may contribute to spinal cord regeneration. Abstract : We find that the levels of the m6A methylase Mettl3 are upregulated following spinal cord injury (SCI) in both zebrafish and mice. Additionally, Mettl3 disruption leads to poor motor function recovery in zebrafish SCI.